The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jgs.16288
|View full text |Cite
|
Sign up to set email alerts
|

Economic Barriers to Antiretroviral Therapy in Nursing Homes

Abstract: OBJECTIVES Our aim was to clarify if persons living with human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) have adequate economic access to antiretroviral therapy (ART) when admitted to nursing homes (NHs). Medicare Part A pays NHs a bundled skilled nursing rate that includes prescription drugs for up to 100 days, after which individuals are responsible for the costs. DESIGN A cross‐sectional study. SETTING NHs. PARTICIPANTS A total of 694 newly admitted long‐stay (>100 d) NH residents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 21 publications
1
6
2
Order By: Relevance
“…We observed that receiving care under the Medicare skilled nursing benefit at baseline was a strong predictor of non‐ART use during NH stays, which confirms previous evidence 8 . People who are admitted to short‐term SNF for post‐acute care are typically covered by Medicare Part A.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…We observed that receiving care under the Medicare skilled nursing benefit at baseline was a strong predictor of non‐ART use during NH stays, which confirms previous evidence 8 . People who are admitted to short‐term SNF for post‐acute care are typically covered by Medicare Part A.…”
Section: Discussionsupporting
confidence: 87%
“…We observed that white residents had a lower likelihood of receiving an ART use compared with black residents. Although this runs counter to prior community‐based studies, 28,29 it is consistent with another NH study 8 . Although we hypothesized whites were more likely to reside in facilities with low HIV experience, our supplementary analyses did not support this explanation.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations